KLASİK ÇAĞ ATİNA HUKUKUNDA OIKOSA İLİŞKİN DÜZENLEMELER. - KÜÇÜKER, Sultan Deniz; GÜLER, Türkan Banu (Tarih İncelemeleri Dergisi)
In Classical Athens, the term oikos referred to the private space as opposed to the public space, and its meanings reflected the socio-economic life of this area. Accordingly, it meant home, family, and property in ancient Greek. This study examines the legal regulations of Athens within the framework of the definitions of oikos. First, it discusses laws related to the institution of marriage, which formed the foundational unit of the social and economic structure of the oikos, as well as laws governing the family and inheritance management. Subsequently, regulations on private property are analyzed. These include citizens’ powers over their property and rules governing commercial and economic activities to protect private property during the exchange of movable and immovable assets. The speeches prepared for the courts of Athens serve as the primary sources of this study, and in addition, epigraphic material is used to attest to the regulations of economic activities. It is commonly known that Athenian government actively interfered with the oikos. This study aims to clarify the dimensions of this relationship by drawing on examples from legal and official historical documents. Thus, it will become more apparent how the polis organized its relations with its citizens on the basis of the oikos.